Math, asked by jisanjay485, 2 months ago

12. If (x + 2), (2x + 3) and (4x + 1) are three consecutive terms of an AP then x is equal to :​

Answers

Answered by riyasaini2120229
3

Answer:

3

Step-by-step explanation:

(2x+3)-(x+2) = (4x+1)-(2x+3)

2x+3-x-2= 4x+1-2x-3

x+1=2x-2

x=3

hope you got it!!!

Answered by ImperialGladiator
72

Answer:

  • x = 3

Explanation:

Given A. P. series :-

  • (x + 2), (2x + 3) and (4x + 1)

We need to find the value of \rm x

We know,

In an A. P. the common difference is same.

Common difference is given by :-

= Second term - First term

Then,

 \rm \therefore \: (2x + 3) - (x + 2) = (4x + 1) - (2x + 3)

Solving further,

 \rm \implies \: (2x + 3) - (x + 2) = (4x + 1) - (2x + 3)

 \rm \implies \: 2x + 3 - x  -  2= 4x + 1 - 2x  -  3

 \rm \implies \: x + 1=  2x  - 2

 \rm \implies \: 2 + 1=  2x  -  x

 \rm \implies \:3 =     x

The value of x is 3

Similar questions